Analisis Prosedur Pemberian Kredit Untuk Menghindari Kredit Macet (Studi Kasus Pada Bank X) - Ningtyas, Septi Ayu; Hascaryani, Tyas Danarti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Regulation of Indonesia Bank 14/22/PBI/2012 explains that all of general bank enlarge the distribution of credit for micro sector business, minor, and medium. However, when the numbers of credit distribution bank persero increases, the risks of non performing loan also increases. So it’s known that the risks of non performing loan are hard constraints which are always faced by banks in distributing credit. In distribution of credit, banks have to apply lending procedures which have been assigned about analysis and consideration to decide the candidate debtors’ worthiness. The purpose of this research is to find out and analyze the regulations and the reality of lending procedures which is applied by bank X. It is also to comprehend and explain the right lending procedures to avoid non performing loan which should be applied by bank X. The research method which is used is qualitative research by using case study of object approach. Techniques of collecting the data in this research are using interviewing, observing, and documenting. Informants for this research are people who are related in loan process. From the research result, it is known that lending procedures which begin from credit applying, credit disbursement until controlling credit still bring out non performing loan. So, within completion of lending procedures, it can decrease non performing loan. Keywords: Lending procedure, Non performing loan